2022
DOI: 10.1055/s-0041-1740032
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Endoscopy in Postoperative Pouch Complications

Abstract: Ileal pouch-anal anastomosis (IPAA) or “J”-pouch as it is commonly referred to, is the treatment of choice in patients with medically refractory ulcerative colitis. IPAA can have infectious, inflammatory, and mechanical complications. Currently, there are no Food and Drug Administration-approved medical therapies for these complications. Surgery that may be eventually required can have significant morbidities due to the complexity of IPAA. Endoscopy is fast emerging as a leading modality of treatment for some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In another series of 8 patients, complete healing of leak was documented in median 2 months-time [79]. Hence EVT can be used for anastomotic leak post IPAA whereas OTSC is to be used if there is leak without any abscess [7].…”
Section: Pouch Leaksmentioning
confidence: 97%
See 2 more Smart Citations
“…In another series of 8 patients, complete healing of leak was documented in median 2 months-time [79]. Hence EVT can be used for anastomotic leak post IPAA whereas OTSC is to be used if there is leak without any abscess [7].…”
Section: Pouch Leaksmentioning
confidence: 97%
“…Endoscopic fistulotomy can be used in short (< 3 cm), superficial (<2 cm thick), simple fistulas like pouch-to-pouch body fistula, perianal fistula and ileo-cecal fistula Role of Interventional IBD in Management of Ulcerative Colitis(UC)-Associated Neoplasia and… DOI: http://dx.doi.org/10.5772/intechopen.106599 [7]. In a study of 29 patients (26 IPAA, 21 having UC) with IBD related fistulas, endoscopic fistulotomy (EFT) with needle knife was successful in healing fistula in nearly 90% patients whereas 10% require surgical intervention [80].…”
Section: Pouch Fistulamentioning
confidence: 99%
See 1 more Smart Citation
“…They can be fibrotic or nonfibrotic (inflammatory) in nature (60). Strictures can be due to ischemia, intraoperative technical difficulties, nonsteroidal anti-inflammatory drug use, or CLDP (10,62,63). Complications from strictures include bowel obstruction, evacuation disorders, pouch dilatation, and bacterial overgrowth (63).…”
Section: Stricturesmentioning
confidence: 99%
“…Despite a reported rate of 38% of stricture frequency in a consecutive series (61), more recent studies observed stricture formation in up to 11.2% of the patients (1,60). Typical locations include the pouch-anal anastomosis, midpouch, and pouch inlet (Figure 4) (10,62). They can be fibrotic or nonfibrotic (inflammatory) in nature (60).…”
Section: Structural Pouch Disordersmentioning
confidence: 99%